2002
DOI: 10.1051/0004-6361:20021449
|View full text |Cite
|
Sign up to set email alerts
|

Near IR spectroscopy of active galactic nuclei

Abstract: Abstract. Using the VLT together with the near infrared instrument ISAAC, we have obtained medium spectral and high spatial resolution observations of a sample of nearby Seyfert galaxies in the H-band. This band is particularly suited for stellar population studies since the stellar component dominates over the AGN nucleus. The H-band also includes the peak contribution from cool stars. The AGN spectra are very rich in strong metallic lines which are sensitive to stellar luminosity class. For 4 out of 5 galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…1), which is a clear signature of type 1 activity. Furthermore, in our previous near-IR study of AGN, we found that the spectrum of NGC 2992 closely resembles Seyfert 1s (Boisson et al 2002). Despite its strong interaction with NGC 2993, NGC 2992 appears to be the oldest galaxy in our present sample.…”
Section: Discussionsupporting
confidence: 54%
“…1), which is a clear signature of type 1 activity. Furthermore, in our previous near-IR study of AGN, we found that the spectrum of NGC 2992 closely resembles Seyfert 1s (Boisson et al 2002). Despite its strong interaction with NGC 2993, NGC 2992 appears to be the oldest galaxy in our present sample.…”
Section: Discussionsupporting
confidence: 54%
“…Most of the previous work at NIR was focused on either active galactic nuclei (AGNs) or objects with very strong star formation, including recent surveys of ultra-luminous infrared galaxies (Goldader et al 1995;Murphy et al 1999Murphy et al , 2001Burston et al 2001), luminous infrared galaxies (Goldader et al 1997;Reunanen et al 2007), starbursts (Engelbracht 1997;Coziol et al 2001), Seyfert galaxies (Ivanov et al 2000;Sosa-Brito et al 2001;Reunanen et al 2002;Boisson et al 2002), LINERs (Larkin et al 1998;Alonso-Herrero et al 2000;Sosa-Brito et al 2001), and interacting galaxies (Vanzi & Rieke 1997;Vanzi et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…The dynamically decoupled core could be the result of inflow of gas into the central regions of the galaxy via, for example, a past minor merger event. For our target, the majority of the stellar population is old and fairly homogeneous, not showing any variations with radius [2]. There is nevertheless indication of a series of previous star formation bursts [3].…”
Section: Pos(seyfert 2012)037mentioning
confidence: 99%